Atypical teratoid/rhabdoid tumor of the central nervous system associated with congenital cataract - Avninder; Zeeba; Vikas; Shruti; Karam (Wolters Kluwer Medknow Publications, 2008)
Atypical teratoid /rhabdoid tumor (AT/RT) of the central nervous system is a rare but highly aggressive neoplasm that usually affects young children and infants and follows a rapidly fatal course. We report a case of AT/RT in a 3-month-old male infant who also had coincidental unilateral congenital cataract even though there was no associated congenital infectious disease.